UNIFORM MODEL OF PLANNING AND MANAGEMENT SYSTEM EDUCATIONAL WORK OF STUDENTS - Korolskyy, V.V.; Bobilev, D.Ye. (Pedagogy of Higher and Secondary Education, 2008)
In the article the done attempt to define going near creation of model of some subsystems of educational process, namely management educational work of students. In quality an entrance a parameter take time which is outlaid by students on the different types of educational work.